Metodología de la enseñanza para el fortalecimiento de la escritura y ortografía en niños de educación general básica - Mármol, Nathaly R. (2023)
Writing and spelling are skills that distinguish the individual within the educational context; however, there are deficiencies in learning and its teaching, a reality that motivated the present qualitative, descriptive and type research, bibliographic review, non-experimental research, with the aim of analyzing the use of active methodologies for learning to write. and spelling in Basic General Education. The categories of analysis were carried out based on each specific objective of the research, which are focused on active writing methodologies, learning strategies and the benefits that strengthen praxis in writing and spelling. With the investigation of different database sources such as scientific articles, journal articles, theses from repositories and books; that are valid for the last 5 years, all focused on the subject and objectives of the essay where information has been collected, describe the factors and explain the benefits of these, thus addressing relevant arguments regarding the study carried out. In accordance with this, achieve in the student active participation in the classroom and the development of individual and collaborative work skills in order to encourage student participation and formation of critical and reflective thinking, and develop the creation of writing texts. whether unpublished or argumentative.